"Networks of Power": A Simulation to Teach About Durable Inequality. Issue 1 (2nd January 2020) - Hamilton, Mark D.
Abstract: This article introduces a class simulation on inequality entitled "Networks of Power." Its usage and effectiveness are analyzed in light of four critical factors: activity complexity, teaching model, learning outcomes, and potential risks . Simulation mechanics are discussed in some detail and complemented with critical reflections on student learning, based on faculty observations, surveys, essays, and related assessments. The concluding analysis centers on lessons learned in administering the simulation in a professionally-focused context and likely benefits and challenges of application in other class settings.